Comparison of 3- to 6-Month Versus 12-Month Dual Antiplatelet Therapy After Coronary Intervention Using the Contemporary Drug-Eluting Stents With Ultrathin Struts: The HOST-IDEA Randomized Clinical Trial. Issue 18 (5th March 2023) - Han, Jung-Kyu; Hwang, Doyeon; Yang, Seokhun; Park, Sang-Hyeon; Kang, Jeehoon; Yang, Han-Mo; Park, Kyung Woo; Kang, Hyun-Jae; Koo, Bon-Kwon; Hur, Seung-Ho; Kim, Weon; Kim, Seok Yeon; et al.
Abstract : Background: Limited data are available on short-term dual antiplatelet therapy (DAPT) after percutaneous coronary intervention using third-generation drug-eluting stents with ultrathin struts and advanced polymer technology. We investigated whether 3- to 6-month DAPT was noninferior to 12-month DAPT after implantation of drug-eluting stents with ultrathin struts and advanced polymer technology. Methods: We performed an open-label, randomized trial at 37 centers in South Korea. We enrolled patients undergoing percutaneous coronary intervention using the Orsiro biodegradable-polymer sirolimus-eluting stents or the Coroflex ISAR polymer-free sirolimus-eluting stents. Patients with ST-segment–elevation myocardial infarction were excluded. Patients were randomly assigned to receive either 3- to 6-month or 12-month DAPT after percutaneous coronary intervention. The choice of antiplatelet medications was at the physician's discretion. The primary outcome was a net adverse clinical event, a composite of cardiac death, target vessel myocardial infarction, clinically driven target lesion revascularization, stent thrombosis, or major bleeding, defined as Bleeding Academic Research Consortium type 3 or 5 at 12 months. The major secondary outcomes were target lesion failure, a composite of cardiac death, target vessel myocardial infarction, clinically driven target lesion revascularization, and major bleeding. Results: A total of 2013 patients (mean age, 65.7±10.5 years; 1487 males [73.9%]; 1110 [55.1%] presented with acute coronary syndrome) were randomly assigned to 3- to 6-month DAPT (n=1002) or 12-month DAPT (n=1011). The primary outcome occurred in 37 (3.7%) patients in the 3- to 6-month DAPT group and 41 (4.1%) in the 12-month DAPT group. The noninferiority of the 3- to 6-month DAPT group to the 12-month DAPT group was met (absolute risk difference, –0.4% [1-sided 95% CI, –∞% to 1.1%]; P <0.001 for noninferiority). There were no significant differences in target lesion failure (hazard ratio, 0.98 [95% CI, 0.56–1.71], P =0.94) or major bleeding (hazard ratio, 0.82 [95% CI, 0.41–1.61], P =0.56) between the 2 groups. Across various subgroups, the treatment effect of 3- to 6-month DAPT was consistent for net adverse clinical event. Conclusions: Among patients undergoing percutaneous coronary intervention using third-generation drug-eluting stents, 3- to 6-month DAPT was noninferior to 12-month DAPT for net adverse clinical event. Further research is needed to generalize this finding to other populations and to determine the ideal regimen for 3- to 6-month DAPT. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02601157.